(untitled) (Journal of Business Management and Accounting, 2014)
This study examined the empirical association between personality traits, work experience, and improvisation. Big five personality traits (Extraversion, Agreeableness, Conscientiousness, Neuroticism, and Openness) and individual work experience were the independent variables; whereas individual improvisation was the dependent variable. Data were collected from middle management level of government officers from various ministries in Putrajaya, Malaysia. Results revealed that Extraversion and Openness had a significant and positive contribution towards improvisation while other traits (Agreeableness, Conscientiousness, and Neuroticism) did not demonstrate a significant association with improvisation. The findings of this study could contribute to the collective knowledge of management and be useful to both theorists and managers.